Advanced fusion cycles for high-beta magnetic systems - Chirkov, A.Yu.; Khvesyuk, V.I. (Вопросы атомной науки и техники, 2002)
Power balance analysis of alternative (not D-T) fusion cycles is carried out to find high efficiency and lowradioactivity cycles for fusion reactors based on high-beta magnetic systems, such as field reversed configuration (FRC), spherical tokamak, etc. Cycles based on reactions D-D, D-³He, D-⁶Li, D-⁷Be, p-⁶Li, p-⁹Be, and p-¹¹B are considered.